Antifungal Susceptibility Testing of Dermatophytes: Establishing a Medium for Inducing Conidial Growth and Evaluation of Susceptibility of Clinical Isolates - Jessup, C. J. (American Society for Microbiology, 2000)
A standardized reference method for dermatophyte in vitro susceptibility testing is lacking. In a previous study, Norris et al. (H. A. Norris, B. E. Elewski, and M. A. Ghannoum, J. Am. Acad. Dermatol. 40(6, part 2):S9–S13) established the optimal medium and other growth variables. However, the earlier study did not address two issues: (i) selection of an optimal medium for conidial formation by dermatophytes and (ii) validation of the method with a large number of dermatophytes. The present study addresses these two points. To select which agar medium best supported conidial growth, representative isolates of dermatophytes were grown on different agars. Preliminary experiments showed that only oatmeal cereal agar supported the production of conidia by Trichophyton rubrum. We tested the abilities of 251 T. rubrum isolates to form conidia using three different cereal agars and potato dextrose agar. Overall, oatmeal cereal and rice agar media were comparable in their abilities to support T. rubrum conidial growth. Next, we used the oatmeal cereal agar for conidial formation along with the optimal conditions for dermatophyte susceptibility testing proposed by Norris et al. and determined the antifungal susceptibilities of 217 dermatophytes to fluconazole, griseofulvin, itraconazole, and terbinafine. Relative to the other agents tested, terbinafine possessed the highest antifungal activity against all of the dermatophytes. The mean ± standard error of the mean MICs of fluconazole, itraconazole, terbinafine, and griseofulvin were 2.07 ± 0.29, 0.13 ± 0.01, 0.002 ± 0.0003, and 0.71 ± 0.05 μg/ml, respectively. This study is the first step in the identification of optimal conditions that could be used for the standardization of the antifungal susceptibility testing method for dermatophytes. Inter- and intralaboratory agreement as well as clinical correlations need to be established.